AN INTEGRAL EUCHARISTIC ECOLOGY - Anthony J. Kelly, (Asian Horizons, 2015)
In the context of Laudato Sí, this article considers the Eucharist in relationship to the theory and practice of integral ecology. It brings together what is too often kept apart: the world and history, matter and spirit, nature and grace, faith and imagination, in the real presence of Jesus in this sacrament, just as the “transubstantiation” anticipates the universal transformation of all things in Christ. The Eucharist is the ever-renewable resource in a world of non-renewable resources as it nourishes the kind of contemplative action required at this criticalmoment in history.